2011
DOI: 10.1111/j.1600-0609.2011.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive treatment with clofarabine/ara‐C combined with reduced‐intensity conditioning and allogeneic stem cell transplantation in patients with high‐risk, relapsed, or refractory acute myeloid leukemia and advanced myelodysplastic syndrome

Abstract: The combination of cytoreductive chemotherapy with reduced-intensity conditioning (RIC) is a highly effective antileukemic therapy. Purpose of this retrospective analysis was to evaluate the antileukemic efficacy and toxicity of clofarabine-based chemotherapy followed by RIC and allogeneic stem cell transplantation (SCT) for high-risk, relapsed, or refractory acute myeloid leukemia (AML) or myelodysplastic syndromes (MDS). From May 2007 until October 2009, a total of 27 patients underwent allogeneic SCT after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 31 publications
3
35
2
1
Order By: Relevance
“…Some retrospective analysis demonstrated that sequential use of cytoreductive chemotherapy and reduced-intensity conditioning (RIC) was highly effective to eradicate leukemia for high-risk, relapsed, or refractory AML patients undergoing allo-HSCT. The long-term survival reached up to 52%, and even higher at 72.7% for those patients in CR1 [39]. Here in our study, IDA-intensified regimen significantly improved the survival in high-risk AML patients.…”
Section: Discussionsupporting
confidence: 57%
“…Some retrospective analysis demonstrated that sequential use of cytoreductive chemotherapy and reduced-intensity conditioning (RIC) was highly effective to eradicate leukemia for high-risk, relapsed, or refractory AML patients undergoing allo-HSCT. The long-term survival reached up to 52%, and even higher at 72.7% for those patients in CR1 [39]. Here in our study, IDA-intensified regimen significantly improved the survival in high-risk AML patients.…”
Section: Discussionsupporting
confidence: 57%
“…Additional studies have also supported use of clofarabine either for cytoreduction or conditioning purposes [23][24][25][26][27][28]. Concerns for increased post-transplant hepatotoxicity in clofarabine-treated patients, given the hepatotoxicity of the drug, have thus far not been substantiated [29].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitation of long-lasting myelosuppression but gain the antileukemic effect of pretransplantation induction chemotherapy, some centers have evaluated AML-like induction chemotherapies, such as anthracycline/cytosine, arabinoside/fludarabine, or clofarabine/cytosine arabinoside-based chemotherapy, followed by only 3 days' rest before performing a RIC and subsequent allogeneic SCT. [55][56][57] With those conditioning regimens and matched related or unrelated donors, 2-year OS rates of 69% and 56% can be achieved. 56,57 Newer agents, such as 5-azacytidine or decitabine, which have been shown to be active in MDS, 58,59 may also be used as pretransplantation cytoreductive therapy.…”
Section: Role Of Cytogenetics and Molecular Genetics On Outcomementioning
confidence: 99%
“…[55][56][57] With those conditioning regimens and matched related or unrelated donors, 2-year OS rates of 69% and 56% can be achieved. 56,57 Newer agents, such as 5-azacytidine or decitabine, which have been shown to be active in MDS, 58,59 may also be used as pretransplantation cytoreductive therapy. However, the CR rate of approximately 10% is much lower than after conventional induction chemotherapy, and the reported trials confirmed the feasibility without significant survival benefit.…”
Section: Role Of Cytogenetics and Molecular Genetics On Outcomementioning
confidence: 99%